Unsur-Unsur Kontroversial dan Penghinaan Terhadap Agama Islam dalam Suluk Gatholoco - Sumarsih Sumarsih (Jumantara: Jurnal Manuskrip Nusantara, 2021)
Suluk Gatholoco is a Javanese text classified as the type of suluk which contains the concepts of Islamic mystical teaching or sufism. The text of the Suluk Gatholoco is presented in a very controversial debate between Koran teachers, they are Kasan Mustahal, Kasan Besari, Ki Dul Jalal and Gatholoco. The debate also took place between Gatholoco and Dewi Perjiwati, a woman who lived in Kresna Cemara cave. She later would become Gatholoco’s wife. Suluk Gatholoco is transcripted into Latin script in Javanese. Suluk Gatholoco published in macapat forms by Tan Khoen Swie in 1959. Suluk Gatholoco become very controversial because the content of the text considered contempt for Islam. Translation and interpretation is needed to identify and classify the content of Suluk Gatholoco in order to find out the content which is contempt for Islam. Literary research method used to understand and interpret the text of Suluk Gatholoco is hermeneutic.  Based on this research it can be known that Suluk Gatholoco is proven to contain elements of contempt for Islam.